Gender and Local Organisations toward Sustainable Rural Development - Riri Amandaria (Equilibrium: Jurnal Pendidikan, 2022)
Local organization and gender participation are two elements that have the significant role for the rural development plan. The objectives of the study are to describe the function and role of the local organizations as a media for participation, job allocation of men and women performed in rural development plan. A case study method was used with the key informants from the local organization committees, target group, and development facilitators. The data collected are the type and form women and men contribution, roles and functions of the local organizations in the rural development plan process, and the activity proposed by men and women. The study indicated that the involvement of men and women in the development plan process encourages community participation in rural development and generating a better development plan. Women have the significant role in the identification of problems and planning, primarily related to social and economic aspect affecting household activities, while men profoundly concern to public infrastructure affecting to economic activities. The involvement of men and women should be a necessity for every rural development because the proposed action planned is based on the local community needs.